Bethe approach study of the mixed spin-1/2 and spin-5/2 Ising system in the presence of an applied magnetic field - Karimou, M.; Yessoufou, R.A.; Oke, T.D.; Kpadonou, A.; Hontinfinde, F. (Condensed Matter Physics, 2016)
The mixed spin-1/2 and spin-5/2 Ising model is investigated on the Bethe lattice in the presence of a magnetic
field h via the recursion relations method. A ground-state phase diagram is constructed which may be needful
to explore important regions of the temperature phase diagrams of a model. The order-parameters, the corresponding response functions and internal energy are thoroughly investigated in order to typify the nature of
the phase transition and to get the corresponding temperatures. So, in the absence of the magnetic field, the
temperature phase diagrams are displayed in the case of an equal crystal-field on the (kBT /|J|, D/|J|) plane
when q = 3, 4, 5 and 6. The model only exhibits the second-order phase transition for appropriate values of
physical parameters of a model. Дослiджується змiшана спiн-1/2
i спiн-5/2
модель на гратцi Бете в присутностi магнiтного поля h, використовуючи метод рекурсивних спiввiдношень. Побудована фазова дiаграма основного стану, яка може бути
використана для дослiдження цiкавих областей температурної фазової дiаграми моделi. Для того, щоб
прокласифiкувати природу фазового переходу та отримати вiдповiднi температури, детально дослiджено параметри порядку, вiдповiднi функцiї вiдгуку i внутрiшню енергiю. Так, при вiдсутностi магнiтного
поля, температурнi фазовi дiаграми є представленi для випадку однакового кристалiчного поля на площинi (kBT /|J|,D/|J|), коли q = 3, 4, 5 i 6. Модель демонструє тiльки фазовий перехiд другого роду для
вiдповiдних значень фiзичних параметрiв моделi.